HUBUNGAN FALSAFAH NASIONAL DENGAN PRAKTIK PENDIDIKAN PADA KURIKULUM MERDEKA - Muhammad Fakhri Ramadhan; Muhammad Sirozi; Abdurrahmansya; Nurul Ahmad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Indonesia's national philosophy serves as the ideological and moral foundation that guides the administration of national education, particularly through the values of Pancasila and the constitutional principles of the 1945 Constitution (UUD 1945). This philosophy emphasizes that education aims not only to enlighten the nation's life but also to shape Indonesian individuals who are characterized, moral, and capable of living harmoniously within diversity. This study aims to comprehensively examine the relationship between the national philosophy and educational practices in Indonesia, including the normative foundation, implementation in the curriculum, the teacher's role as a value internalizer, challenges faced, as well as its strategic relevance in human resource development. This study employs a library research method by reviewing scientific literature published in the past ten years, including academic books, national and international journals, and relevant research reports. The study results indicate that the national philosophy serves as a fundamental guide in formulating goals, curriculum, and learning practices. The values of Pancasila are operationalized through the Merdeka Curriculum, the Pancasila Student Profile, and project-based learning that emphasizes character development, critical thinking, creativity, collaboration, and spirituality. Teachers play an important role as models, value facilitators, and agents of social transformation in ensuring that the internalization of values occurs meaningfully. However, the implementation of the national philosophy still faces various challenges, such as policy-practice gaps, limitations in teacher competencies, the influence of individualistic digital culture, socio-cultural heterogeneity, and educational facility disparities. Nevertheless, strengthening the application of the national philosophy is considered strategic in developing superior human resources with character, global competitiveness, and contributions to national development.